the PENGARUH VARIASI MENU, HARGA DAN SUASANA TEMPAT TERHADAP KEPUASAN PELANGGAN YOKINA COFFEE AND EATERY DI KOTA PROBOLINGGO: PENGARUH VARIASI MENU, HARGA DAN SUASANA TEMPAT TERHADAP KEPUASAN PELANGGAN YOKINA COFFEE AND EATERY DI KOTA PROBOLINGGO - Sri Sandyawati, Novi; Amalia Hapsari, Farasandya; Anam, M. Khoirul; Wicaksono, Eko; Irawan, Sandi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Business has grown rapidly and undergone constant transformation. The food and beverage industry is a promising one. Fast food cafes are currently a lifestyle trend for adults. Fast food cafes are considered dining establishments that can provide the desired relaxed atmosphere. Cafes can be a place to relax with friends or family, socialize with business associates, or even simply enjoy the solitude. The purpose of this study is to determine the Effect of Menu Variation, Price and Place Atmosphere on Customer Satisfaction at Yokina Coffee and Eatery. This study uses a descriptive method with a quantitative approach. Data collection techniques in this study use questionnaires, interviews, and observations. While the data analysis used is a descriptive technique that has 3 independent variables, namely X1 (Menu Variation), X2 (Price), X3 (Place Atmosphere) and 1 dependent variable, namely Y (Customer Satisfaction). The results of this study can be concluded that Menu Variation can have a positive effect on customer satisfaction. Price can have a very positive and significant effect on customer satisfaction. Place atmosphere has a very positive and significant effect on customer satisfaction, while the price variable has a very positive and significant effect on customer satisfaction, seen from the value of the regression coefficient results which are greater than the Menu variation and place atmosphere variables.